Indigenous Thought, Appropriation, and Non-Aboriginal People - Haig-Brown, Celia (Canadian journal of education, 2010)
In this article, I explore the question, “What is the relationship between appropriation of Indigenous thought and what might be called ‘deep learning’ based in years of education in Indigenous contexts.” Beginning with an examination of meanings ascribed to cultural appropriation, I bring texts from Gee on secondary discourses, Foucault on the production of discourse, and Wertsch on the deep structures underpinning discourse into conversation with critical fieldwork experiences extracted from years of research and teaching. Ultimately hopeful, I conclude the article with direction from Indigenous scholars on appropriate cultural protocol in the use of Indigenous knowledges by non-Aboriginal people in educational contexts.